2022
DOI: 10.1080/14686996.2022.2062576
|View full text |Cite
|
Sign up to set email alerts
|

Science of 2.5 dimensional materials: paradigm shift of materials science toward future social innovation

Abstract: The past decades of materials science discoveries are the basis of our present society – from the foundation of semiconductor devices to the recent development of internet of things (IoT) technologies. These materials science developments have depended mainly on control of rigid chemical bonds, such as covalent and ionic bonds, in organic molecules and polymers, inorganic crystals and thin films. The recent discovery of graphene and other two-dimensional (2D) materials offers a novel approach to synthesizing m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
55
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 49 publications
(55 citation statements)
references
References 193 publications
(231 reference statements)
0
55
0
Order By: Relevance
“…Another STEM study indicated that new FeCl 2 and FeOCl phases form when BLG is intercalated with FeCl 3 . Therefore, crystalline structures and phase transitions that have never been reported are expected in the confined 2D nanospace of BLG, providing the opportunity to extend a field of materials science …”
mentioning
confidence: 99%
See 3 more Smart Citations
“…Another STEM study indicated that new FeCl 2 and FeOCl phases form when BLG is intercalated with FeCl 3 . Therefore, crystalline structures and phase transitions that have never been reported are expected in the confined 2D nanospace of BLG, providing the opportunity to extend a field of materials science …”
mentioning
confidence: 99%
“…Intercalation of Na ions, which is expected to be the basis for a new type of battery, has been demonstrated using stacks of functionalized graphene sheets . Thus, the use of the interlayer nanospace further expands the potential applications of the multilayers of 2D materials …”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, surface modification of two-dimensional materials by using low molecular weight species was found to enable tuning of the physical properties . These designs of two-dimensional-based materials have started to be investigated widely …”
mentioning
confidence: 99%